Understanding anhedonia in major depressive disorder in Japan: epidemiology and unmet needs from patients’ and physicians’ perspectives - Mami Kasahara-Kiritani; Tadafumi Kato; Akihide Wakamatsu; Thomas Webb; Keira Herr; Lawrence Vandervoort; Nan Li (BMC Psychiatry)
Abstract Background Anhedonia (ANH), one of the core symptoms of major depressive disorder (MDD), poses a significant health challenge. We evaluated the prevalence of ANH among MDD patients in Japan, and elucidated patient journey from patients’ and physicians’ perspective. Methods This cross-sectional observational study (April-May 2023) utilized a self-reported, online-based survey targeting the general population (non-physicians) and physicians. The general population (aged ≥ 18 years) were screened for MDD using Patient Health Questionnaire-9 (PHQ-9 ≥ 10); MDD patients were further screened for ANH using Snaith-Hamilton Pleasure Scale (SHAPS; MDD-ANH: SHAPS > 2, MDD non-ANH: SHAPS ≤ 2). The age- and gender-weighted prevalences of MDD and MDD-ANH, patient journey, and treatment goals and satisfaction between patients and physicians were reported. P-value < 0.05 was considered statistically significant. Results The prevalence of MDD was 3.4% (n = 514; N = 15,266) and the prevalence of ANH in MDD was 66.9% (n = 344). Mean (± standard deviation) age of MDD-ANH patients (n = 282) was 46.1 ± 12.5 years, while for MDD non-ANH patients (n = 50) was 49.6 ± 8.5 years. Physicians (n = 60) had mean 21.9 years of experience working as psychiatrists. Physicians reported that 33.9% of their MDD patients had anhedonia. MDD-ANH patients scored significantly higher (p < 0.05) than MDD non-ANH patients on all PHQ-9 items, except for feeling tired/having little energy and poor appetite/overeating. A higher percentage of MDD-ANH patients reported current prescription use for depression than MDD non-ANH patients (67.0% vs. 51.3%; p = 0.0677). Treatment duration with multiple prescriptions was significantly longer in MDD-ANH than MDD non-ANH patients (102.1 ± 89.8 vs. 53.8 ± 33.7 months; p = 0.0035). The majority of physicians (90.0%) reported that they do not focus on treating anhedonia separately from MDD. Patients with MDD-ANH perceived “reduce psychological anxiety”, “control depressed mood”, and “improve sleep quality” as more important treatment goals, compared to physicians’ importance to avoid suicidal thoughts, restore normal social function, and regain interest in hobbies. Treatment satisfaction levels were higher among physicians than MDD-ANH patients across all treatment goals. Conclusion This study in Japan reported high prevalence of ANH among MDD patients which was significantly underestimated by physicians. Discordances in treatment goals and satisfaction were observed between physicians and MDD patients, highlighting the need for aligning patient and physician expectations. Trial registration: Not applicable.